Being in time : dynamical models of phenomenal experience - Edelman, Shimon; Fekete, Tomer; Zach, Neta (Advances in consciousness research, 2012)
Given that a representational system's phenomenal experience must be intrinsic to it and must therefore arise from its own temporal dynamics, consciousness is best understood -- indeed, can only be understood -- as being in time. Despite that, it is still acceptable for theories of consciousness to be summarily exempted from addressing the temporality of phenomenal experience. The chapters comprising this book represent a collective attempt on the part of their authors to redress this aberration. The diverse treatments of phenomenal consciousness range in their methodology from philosophy, throu.